PHARMACEUTICAL MONITORING OF EYE FLOATERS - K, Vinod Kumar; S, Gayatri Sai Vishnavi; P, Sravani; Syed, Sofiya Sulthana; Y, Ramya (International Journal of Zoology, Environment and Life Sciences, 2026)
Eye floaters are small, shadow-like shapes that appear to drift across a person’s field of vision. They are commonly described as spots, threads, cobwebs, or squiggly lines and are most noticeable when looking at a bright or plain background. Floaters occur due to changes in the vitreous humor, the gel-like substance that fills the eye. With aging, the vitreous gradually becomes more liquid, causing tiny fibers within it to clump together and cast shadows on the retina, which are perceived as floaters. Although eye floaters are generally harmless and a natural part of the aging process, a sudden increase in floaters, flashes of light, or loss of peripheral vision may indicate serious conditions such as retinal detachment or vitreous hemorrhage. Diagnosis typically involves a comprehensive eye examination, including dilated fundus evaluation. In most cases, no treatment is required, and floaters become less noticeable over time. However, in severe or vision-impairing cases, treatment options such as vitrectomy or laser therapy may be considered. Understanding the causes, symptoms, and potential complications of eye floaters is essential for early detection and prevention of vision-threatening conditions.